PEMBERDAYAAN WARGA MASYARAKAT AKAN PENTINGNYA SANITASI BAGI LINGKUNGAN DI KELURAHAN PINDRIKAN LOR, SEMARANG TENGAH, SEMARANG - Muldiyanto, Agus; Budiningrum, Diah Setyati; Kustirini, Anik (Jurnal Abdimas Bina Bangsa, 2024)
Sanitation, both household sanitation and environmental sanitation, are related units that influence each other. Some of the problems in Pindrikan Lor Village include a relatively dense population of ±5,930 people, some areas where the houses are close together, rubbish, puddles of water or flooding when it rains and still stunting in the area, this will of course have a big impact sanitation. This PkM aims to provide a correct understanding of the importance of sanitation for both the household and the environment, as well as providing prevention of the causes, impacts and ways of preventing it. Qualitative and quantitative methods, qualitative include observation stages in the field looking at the condition of the housing environment, drainage and waste, as well as asking directly to local residents, while for quantitative the test method is used regarding understanding both tests, before / pretest and after the material is explained / post-test, before the event closes. The activity was carried out on May 14 2024, on Floor 2 of the Village Office, attended by representatives of RT, RW, PKK and Village Heads and their staff, totaling around 40 participants. The results of the discussion, pre-post-test on Community Service included residents being enthusiastic in asking questions according to the theme and responding well, while the results of the pre-post-test were for understanding of sanitation to 84.63%, understanding of the impact of poor sanitation increased to 76.90%.